(untitled) (Journal of Economic Research & Business Administration, 2017)
The article deals with the main issues of international experience in public-private partnership (PPP) and its feasibility in innovation. This article examines the experience of the following foreign countries: USA, Canada, Great Britain, Germany, France, Chile, Brazil, South Africa, India, Japan, China, Korea, Russia. The periods of development and forms of PPP, their main advantages and weaknesses are considered, as well as a scheme of government-business relations in the sphere of innovations. It is concluded that in many cases PPP makes it possible to reduce a large part of budget expenditures and allows to attract private business in those areas that are less attractive for them, but are significant for the society as a whole. In this paper, the following methods of scientific knowledge were used: comparison, cause-effect relationships, observation and grouping.